Musical Creativity and Character Education Values in Performing Arts Activities at SMA Negeri 1 Kedungwuni - Afwa, Mughny El.; Utomo, Udi; Cahyono, Agus (Universitas Negeri Semarang, 2021)
This study aims to analyze the process of students' musical creativity and the value of character education through performing arts activities at SMA Negeri 1 Kedungwuni. This study uses a qualitative method. The data were collected by using observation, interview, and document study techniques. The data analysis procedures used data reduction, data presentation, and data verification. The validity of the data used is triangulation, data sources, and theory. The results showed that the process of musical creativity in performing arts activities at SMA Negeri 1 Kedungwuni was carried out in 4 stages. In the first stage, namely preparation, students chose songs and determined what musical arrangements that matched to the theme determined by the teacher. In the second stage, namely incubation, students determined the solution to the problem of music, drama, and dance collaboration arrangements to the teacher through discussion. In the third stage, students determined the musical instruments used, arranged arrangements, and practiced. The last stage was verification of the work of musical creativity which was carried out through the pre-general rehearsal and general rehearsal. Character education values that were formed during the preparation process and performing arts activities are: (1) the value of discipline, (2) the value of creative, (3) the value of cooperation, and (4) the value of responsibility.